Perovskite solar cell and its manufacturing method
By incorporating a conductive barrier layer between the electron transfer layer and the source electrode in perovskite solar cells, the stability and efficiency issues associated with conventional metal oxide-based electron transfer layers are addressed, resulting in improved long-term performance and reduced manufacturing costs.
Patent Information
- Application Number
- JP2023562883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-13
- Filing Date
- 2022-03-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-03-29
AI Technical Summary
Conventional perovskite solar cells face challenges with stability and manufacturing costs due to the use of metal oxides for electron transfer layers, which require complex processes, high-energy consumption, and can damage the light absorbing layer.
The introduction of a conductive barrier layer between the electron transfer layer and the source electrode, formed using materials like ITO, FTO, or ATO, prevents electrode penetration and ion migration, thereby enhancing the stability and efficiency of the solar cell without the need for fullerene deposition layers.
This solution improves the long-term stability and photoelectric conversion efficiency of perovskite solar cells by reducing unnecessary light absorption and maintaining the integrity of the light absorbing layer, while also simplifying the manufacturing process and reducing costs.
Smart Images

Figure 0007665045000008 
Figure 0007665045000009 
Figure 0007665045000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a perovskite solar cell including an electron transport layer formed of a specific component and a conductive barrier layer introduced between the electron transport layer and a source electrode, and a method for manufacturing the same. [Background technology]
[0002] 2. Description of the Related Art In order to solve the global environmental problems caused by the depletion of fossil energy and its use, active research is being conducted into renewable, clean alternative energy sources such as solar energy, wind power, and hydroelectric power.
[0003] Among these, interest in solar cells that directly convert sunlight into electrical energy has increased significantly. Here, a solar cell refers to a cell that absorbs light energy from sunlight and generates a current and voltage using the photovoltaic effect that generates electrons and holes.
[0004] Currently, it is possible to manufacture np diode type silicon (Si) single crystal-based solar cells with a light energy conversion efficiency of over 20% and they are actually used for solar power generation, and there are also solar cells using compound semiconductors such as gallium arsenide (GaAs) that have even better conversion efficiency. However, such inorganic semiconductor-based solar cells require highly refined materials to achieve high efficiency, which consumes a lot of energy to refine the raw materials, and the process of using the raw materials to make single crystals or thin films requires expensive processing equipment, which limits the reduction in the manufacturing cost of solar cells and has been an obstacle to large-scale use.
[0005] As a result, in order to produce solar cells at low cost, it is necessary to significantly reduce the costs of the materials and manufacturing processes used as the core of the solar cell. As such, research is underway into perovskite solar cells, which can be manufactured using low-cost materials and processes instead of inorganic semiconductor-based solar cells.
[0006] Recently, perovskite solar cells that use the perovskite-structured halide compound (NH3CH3)PbX3 (X=I, Br, Cl) as a photoactivator have been developed, and research is being conducted for commercialization. The general structural formula of perovskite is the ABX3 structure, where anions are located at the X site, large cations are located at the A site, and small cations are located at the B site.
[0007] Perovskite solar cells, which are organometallic halide compounds with the molecular formula (CH3NH3)PbX3, were first used as photoactive materials in solar cells in 2009. Since then, solid-state perovskite solar cells with the current structure were developed in 2012, and their efficiency has improved rapidly. Conventional perovskite solar cells use metal oxides as the electron transport layer and organic or polymeric materials such as spiro-OMETAD as the hole transport layer (HTL). That is, a metal oxide porous film or thin film is fabricated on a transparent electrode such as FTO, coated with a perovskite material, and then coated with a hole transport layer, after which an electrode layer such as gold (Au) or silver (Ag) is evaporated onto the film.
[0008] The key issues for commercialization of perovskite solar cells are ensuring stability and flexible technology. Conventional electron transport layers formed using metal oxides on top of the photoactive layer are formed by depositing or coating a metal oxide on top of the photoactive layer (or light absorbing layer) and then forming a separate organic binder coating layer on top of it. However, when forming the solar cell by vapor deposition of metal oxide, the manufacturing process becomes complicated, which significantly increases the manufacturing cost, and the light absorbing layer may be damaged by physical and chemical energy generated during the vapor deposition process. In addition, the method of forming the organic binder coating layer requires high-temperature heat treatment to form the coating layer, but perovskite materials decompose at high temperatures of 200°C or higher, which reduces the flexibility of the solar cell and narrows the range of application of perovskite solar cells.
[0009] In addition, in general, fullerene (C) is used to form the electron transport layer without damaging the light absorption layer when manufacturing perovskite heterojunction solar cells. 60 ) is formed as a conductive barrier layer through deposition, but fullerenes have high optical absorption and cause unwanted light absorption (parasitic absorption), which increases the short-circuit current density J of solar cells. sc There are problems that reduce efficiency, such as: Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made to overcome the above-mentioned problems, and aims to provide a perovskite solar cell and a method for manufacturing the same, which ensures high efficiency by forming a conductive barrier layer between an electron transport layer made of a specific material and a source electrode without forming a fullerene deposition layer that reduces the Jsc of the solar cell. [Means for solving the problem]
[0011] In order to solve the above problems, the perovskite solar cell of the present invention includes a structure in which a hole transport layer, a perovskite light absorbing layer, an electron transport layer, and a source electrode are laminated in this order, and a conductive barrier layer may be formed between the source electrode and the electron transport layer.
[0012] In one preferred embodiment of the invention, the electron transport layer may comprise surface-modified SnO2 nanoparticles.
[0013] In a preferred embodiment of the invention, the electron transport layer may have an average thickness of 100 nm or less.
[0014] In a preferred embodiment of the present invention, the electron transport layer may have a light transmittance of 88 to 95% for a wavelength of 500 to 550 nm when the electron transport layer has a thickness of 20 to 30 nm.
[0015] In a preferred embodiment of the present invention, the surface of the electron transport layer may have a root mean square (RMS) roughness of 25 nm or less.
[0016] In a preferred embodiment of the present invention, the conductive barrier layer may be a transparent thin film formed by vapor deposition of ITO (indium tin oxide), FTO (fluorine doped tin oxide), ATO (Sb2O3 doped tin oxide), GTO (gallium doped tin oxide), ZTO (tin doped zinc oxide), ZTO:Ga (gallium doped ZTO), IGZO (indium gallium zinc oxide), IZO (indium doped zinc oxide) or AZO (aluminum doped zinc oxide).
[0017] In a preferred embodiment of the present invention, the conductive barrier layer may have an average thickness of 50 to 110 nm.
[0018] In a preferred embodiment of the present invention, the surface of the conductive barrier layer may have an RMS roughness of 30 nm or less.
[0019] In a preferred embodiment of the present invention, the conductive barrier layer may have a sheet resistance of 80 Ω / sq or less.
[0020] In a preferred embodiment of the present invention, the perovskite solar cell of the present invention may be a pin-structured perovskite solar cell, an inverted structured perovskite solar cell, a tandem perovskite solar cell or a tandem silicon / perovskite heterojunction solar cell.
[0021] In a preferred embodiment of the present invention, when the perovskite solar cell of the present invention is an inverted structure perovskite solar cell, it may have a structure in which a drain electrode, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, a conductive barrier layer and a source electrode are laminated in this order.
[0022] In a preferred embodiment of the present invention, when the perovskite solar cell of the present invention is a tandem silicon / perovskite heterojunction solar cell, it may have a structure in which a drain electrode, a silicon solar cell, a recombination layer, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, a conductive barrier layer and a source electrode are stacked in this order.
[0023] Another object of the present invention relates to a method for manufacturing the above-mentioned perovskite solar cell, which can be manufactured by carrying out a process including the steps of: coating an upper part of a perovskite light-absorbing layer of a laminate including a hole transport layer and a perovskite light-absorbing layer with a coating agent for forming an electron transport layer to form an electron transport layer; forming a transparent thin-film conductive barrier layer on the upper part of the electron transport layer through a deposition process; and forming a source electrode on the upper part of the conductive barrier layer.
[0024] In a preferred embodiment of the present invention, the coating can be performed by a solution coating process, the coating can be performed by a solution coating method such as spin coating, blade coating or bar coating.
[0025] In a preferred embodiment of the present invention, the coating agent for forming an electron transport layer may contain 0.50 to 3.00% by weight of a surface-modified metal oxide and the remaining amount of an organic solvent. Effect of the Invention
[0026] In the perovskite solar cell of the present invention, an electron transport layer can be formed by a solution coating method using a coating agent for forming an electron transport layer, which can form an ultra-thin film through low-temperature heat treatment. When the electron transport layer is formed, damage to the light absorption layer can be prevented. The conductive barrier layer formed between the electron transport layer and the source electrode prevents electrode penetration and ion migration, thereby preventing a decrease in the photoelectric conversion efficiency of the solar cell and providing excellent long-term performance stability of the solar cell. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a TEM measurement image of the SnO2 nanoparticles produced in Example 1. [Diagram 2] FIG. 2 is an XRD measurement graph of the SnO2 nanoparticles produced in Example 1. [Diagram 3] FIG. 3 is an FT-IR measurement graph of the surface-modified SnO2 nanoparticles produced in Example 1. [Figure 4] FIG. 4(a) is a photograph of a solution of unmodified SnO2 nanoparticles dispersed in isopropane alcohol, and (b) is a photograph of the coating solution for forming the electron transport layer prepared in Example 1. [Diagram 5] FIG. 5 shows the results of measuring the transmittance of a thin film produced using the coating liquid for forming an electron transport layer in Example 1. [Figure 6] FIG. 6 shows SEM measurement images of the solar cells of Production Example 1 and Comparative Production Example 1. [Figure 7] FIG. 7 shows SEM measurement images of the solar cells of Production Example 1 and Comparative Production Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will now be described in more detail.
[0029] Conventional perovskite solar cells use fullerene (C) to form the electron transport layer without damaging the light absorption layer.60 ), C 60 and SnO2 double deposition layer, C 60 However, fullerenes have a high optical absorption and cause unnecessary light absorption (parasitic absorption), which increases the short-circuit current density J of solar cells. sc There was a problem of reducing the following:
[0030] Thus, the present invention relates to fullerene (C 60 The present invention relates to a perovskite solar cell that prevents electrode penetration and ion migration by eliminating an ultra-thin film layer, optimizing the material of the electron transport layer, and forming a conductive barrier layer between the electron transport layer and the source electrode, thereby preventing a decrease in photoelectric conversion efficiency and improving the long-term performance stability of the solar cell.
[0031] The perovskite solar cell of the present invention may be a pin-type perovskite solar cell, an inverted type perovskite solar cell, a tandem type perovskite solar cell, or a tandem type silicon / perovskite heterojunction solar cell, and is a solar cell including a laminate structure in which a hole transport layer (HTL or hole transport layer), a perovskite light absorbing layer, an electron transporting layer (ETL), a conductive barrier layer (passivation layer), and a source electrode are laminated in this order.
[0032] In a preferred embodiment, when the solar cell of the present invention is an inverted perovskite solar cell, the laminate may be laminated on an upper portion of a drain electrode.
[0033] In addition, the inverted perovskite solar cell may be formed by stacking a conductive substrate, a drain electrode, a hole transport layer, a light absorbing layer, an electron transport layer, and a source electrode in order to form one set, and the set may be stacked in a single layer or multiple layers.
[0034] In yet another preferred embodiment, when the solar cell of the present invention is a tandem silicon / perovskite heterojunction solar cell, a drain electrode, a silicon solar cell, a recombination layer, and the stack may be stacked in this order.
[0035] Based on the method for producing the laminate constituting the perovskite solar cell of the present invention, The present invention will be described in detail based on the above, and the laminate can be manufactured by carrying out processes including: a step of forming an electron transport layer by coating an upper portion of a perovskite light absorbing layer of a laminate including a hole transport layer and a perovskite light absorbing layer with a coating agent for forming an electron transport layer to form an electron transport layer; a step of forming a transparent thin film conductive barrier layer on the upper portion of the electron transport layer through a deposition process; and a step of forming a source electrode on the upper portion of the conductive barrier layer.
[0036] The hole transport layer (HTL) may comprise inorganic and / or organic hole transport materials. The inorganic hole transport materials include nickel oxide (NiO x ), CuSCN, CuCrO2 and CuI.
[0037] The organic hole transport material may be a carbazole derivative, a polyarylalkane derivative, a phenylenediamine derivative, an arylamine derivative, an amino-substituted chalcone derivative, a styrylanthracene derivative, a fluorene derivative, a hydrazone derivative, a stilbene derivative, a silazane derivative, an aromatic tertiary amine compound, a styrylamine compound, an aromatic dimethylidine-based compound, a porphyrin-based compound, a phthalocyanine-based compound, a polythiophene derivative, a polypyrrole derivative, a polyparaphenylenevinylene derivative, pentacene, coumarin 6, 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, zinc phthalocyanine (ZnPC), copper phthalocyanine (CuPC), titanium oxide (TiOPC), etc. phthalocyanine), Spiro-MeOTAD(2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), F16CuP C(copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H, 31H-phthalocyanine), SubPc(boron P3HT(poly[3-hexylthiophene]), MDMO-PPV(poly[2-methoxy-5-(3',7'-dimethyloctyloxyl)]-1,4-phenylene vinylene)、MEH-PPV(poly[2-methoxy-5-(2’’-ethylhexyloxy)-p-phenylene vinylene])、P3OT(poly(3-octyl thiophene))、POT(poly(octyl thiophene))、P3DT(poly(3-decyl thiophene))、P3DDT(poly(3-dodecyl thiophene)、PPV(poly(p-phenylene vinylene))、TFB(poly(9,9’-dioctylfluorene-co-N-(4-butylphenyl)diphenyl amine)、ポリアニリン(Polyaniline)、Spiro-MeOTAD([2,22’,7,77’-tetrkis(N,N-di-pmethoxyphenyl amine)-9,9,9’-spirobi fluorine])、CuSCN,CuI,PCPDTBT(Poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b’]dithiophene-2,6-diyl]],Si-PCPDTBT(poly[(4,4’-bis(2-ethylhexyl)dithieno[3,2-b:2’,3’-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl])、PBDTTPD(poly((4,8-diethylhexyloxyl)、PFDTBT(poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4’,7,-di-2-thienyl-2’,1’,3’-benzothiadiazole)])、PFO-DBT(poly[2,7-9,9-(dioctyl-fluorene)-alt-5,5-(4’,7’-di-2-thienyl-2’,1’,3’-benzothiadiazole)])、PSiFDTBT(poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5'-diyl]), PCDTBT(Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl]), PFB(poly(9,9'-dioctyl fluorene-co-bis(N,N'-(4,butylphenyl))bis(N,N'-phenyl-1,4-phenylene)diamine), F8BT(poly(9,9'-dioctylfluorene-cobenzothiadiazole), PEDOT(poly(3,4-ethylenedioxythiophene)), PEDOT:PSS The polymer may include poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate), PTAA (poly(triarylamine)), 2-PACz, and / or MeO-2PACz.
[0038] The hole transport layer can be formed by a coating method, a vacuum deposition method, or the like. The coating method can be a gravure coating method, a bar coating method, a printing method, a spray coating method, a spin coating method, a dip coating method, a die coating method, or the like.
[0039] Next, the light absorbing layer may include a perovskite material generally used in light absorbing layers of solar cells, or, as a preferred example, may include a perovskite material represented by the following chemical formula 2.
[0040] [Chemical formula 2] CMX3
[0041] In formula 2, C is a monovalent cation, which may include amines, ammonium, Group 1 metals, Group 2 metals, and / or other cations or cation-like compounds, and is preferably formamidinium (FA), methylammonium (MA), FAMA, CsFAMA, or N(R)4.+ (wherein R may be the same or different groups, and R is a linear alkyl group having 1 to 5 carbon atoms, a branched alkyl group having 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group, an alkoxyphenyl group, or an alkyl halide); Furthermore, M in Chemical Formula 2 is a divalent cation and may include one or two selected from Fe, Co, Ni, Cu, Sn, Pb, Bi, Ge, Ti, Eu, and Zr.
[0042] In addition, X in Chemical Formula 2 is a monovalent anion and may contain one or more halide elements and / or Group 16 anions selected from F, Cl, Br, and I. In a preferred example, X is I x Br 3-x (0≦x≦3).
[0043] In addition, a preferred embodiment of the formula 2 is FAPbI x Br 3-x (0≦x≦3), MAPbI x Br 3-x (0≦x≦3), CsMAFAPbI x Br 3-x (0 ≦x≦3), CH3NH3PbX3 (X=Cl, Br, I, BrI2, or Br2I), CH3NH3SnX3 (X=Cl, Br or I), CH(=NH)NH3PbX3 (X=Cl, Br, I, BrI2, or Br2I), CH(=NH)NH3SnX3 (X=Cl, Br or I).
[0044] In the solar cell of the present invention, the light absorbing layer is made of the same perovskite material. The light absorbing layer may be a single layer formed of a single perovskite material, or may be a multi-layer structure in which multiple layers made of different perovskite materials are stacked. The light absorbing layer may contain a different type of perovskite material different from the single perovskite material, the perovskite material having a pillar shape such as a columnar, plate, needle, wire or rod shape.
[0045] Next, the coating agent for forming an electron transport layer is a dispersion liquid in which surface-modified metal oxide nanoparticles are dispersed in an organic solvent, and contains, based on the total weight, 0.50 to 3.00 wt % of the surface-modified metal oxide and the remainder of the organic solvent, preferably 0.58 to 2.88 wt % of the surface-modified metal oxide and the remainder of the organic solvent, and more preferably 0.65 to 1.91 wt % of the surface-modified metal oxide and the remainder of the organic solvent.
[0046] Here, if the content of the surface-modified metal oxide in the coating agent is less than 0.50 wt%, the SnO2 content is insufficient, which may cause a problem of the light absorption layer being exposed during the formation of the SnO2 thin film. If it exceeds 3.00 wt%, the thickness of the SnO2 thin film increases, which may cause a problem of a decrease in the short circuit current Jsc and open circuit voltage Voc of the solar cell. Therefore, it is preferable to include the surface-modified metal oxide within the above range.
[0047] In addition, the organic solvent may have a dielectric constant of 20 or less, preferably 5 to 15. Specific examples of such organic solvents include isopropyl alcohol, butyl alcohol, 2-methoxyethanol, and ethyl acetate, which may be used alone or in combination as the organic solvent of the present invention. Furthermore, when a solvent with a dielectric constant of more than 20 is used, the attraction between the SnO2 particles and the polar solvent increases, which may cause a problem of aggregation of the SnO2 particles (reduction in dispersibility and dispersion stability), and may cause a problem of decomposition of the perovskite material as the light absorbing layer in the polar solvent during the formation of the SnO2 thin film.
[0048] The surface-modified metal oxide nanoparticles can be prepared by a process including: a step of preparing metal oxide nanoparticles; and a step of reacting the metal oxide with a compound represented by the following Chemical Formula 1 to prepare the surface-modified metal oxide nanoparticles.
[0049] [ka]
[0050] In the above formula 1, R 1 ~R 5 are independently a hydrogen atom or a halogen atom, preferably a halogen atom, and more preferably -F. Furthermore, n is an integer of 0 to 5, preferably 0 to 3, and more preferably 0 to 2.
[0051] More specifically, step 1 can be prepared by carrying out a process including: step 1-1 of mixing a metal precursor and ultrapure water to prepare a metal precursor solution; step 1-2 of adding a basic aqueous solution to the metal precursor solution to prepare a reaction solution; and step 1-3 of hydrothermally synthesizing the reaction solution and obtaining metal oxide nanoparticles from the hydrothermal synthesis product.
[0052] In the method for preparing surface-modified metal oxide nanoparticles, the metal precursor solution in step 1-1 may include a metal precursor and ultrapure water, and the concentration of the metal precursor in the metal precursor solution may be may be 0.15 to 0.7 M, preferably 0.16 to 0.5 M. If the concentration of the metal precursor in the metal precursor solution is less than 0.15 M, the yield of metal oxide nanoparticles may be too small, whereas if the concentration of the metal precursor in the metal precursor solution is more than 0.7 M, the viscosity of the metal precursor aqueous solution increases, and metal oxide nanoparticles may be formed with non-uniform sizes during production under the same process conditions, making it difficult to obtain uniform nanoparticles.
[0053] In the method for producing surface-modified metal oxide nanoparticles, the basic aqueous solution in the 1-2 steps may include one or more selected from a KOH aqueous solution, a NaOH aqueous solution, a hydrazine aqueous solution, and an NH4OH aqueous solution. The amount of the basic aqueous solution used is added to the metal precursor solution so that the pH of the reaction solution is 8.0 or more, preferably pH 8.0 to pH 9.0, and more preferably pH 8.2 to 8.8. If the pH is less than 8, the yield of metal oxide nanoparticles may be too small, and the metal precursor solution may gel and the stirring may not be good. If the pH is too high, the particle size of the metal oxide particles may become very large.
[0054] In the method for producing surface-modified metal oxide nanoparticles, the hydrothermal synthesis in steps 1-3 can be carried out by applying a general hydrothermal synthesis method used in the art, and the hydrothermal synthesis is carried out at 100-200°C, preferably 120-190°C, more preferably 140-180°C for 6-48 hours, preferably 10-24 hours, more preferably 12-18 hours. Here, if the hydrothermal synthesis temperature is less than 100°C, there may be a problem of low crystallinity of the metal oxide, and if it exceeds 200°C, there may be a problem of the size of the metal oxide particles increasing. In addition, if the hydrothermal synthesis time is less than 6 hours, there may be a problem of the yield of the metal oxide nanoparticles being too low, and if it exceeds 48 hours, there may be a problem of the size of the hydrothermal synthesis product being too large, so it is better to carry out the hydrothermal synthesis within the above time.
[0055] The metal oxide nanoparticles obtained through the hydrothermal synthesis can be repeatedly washed 3 to 5 times using ultrapure water and ethanol.
[0056] The metal oxide nanoparticles thus obtained may have an average particle size of 2 to 10 nm, preferably an average particle size of 2 to 8 nm, and more preferably an average particle size of 3 to 5 nm.
[0057] In addition, the metal oxide of the metal oxide nanoparticles may be an oxide of a metal including one or more selected from tin (Sn), titanium (Ti), zinc (Zn), cerium (Ce), zirconium (Zr), strontium (Sr), zinc (Zn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), aluminum (Al) and gallium (Ga). In one embodiment, the metal oxide may include SnO2, TiO2, ZnO, CeO2 and / or Zn2SnO4, etc., and preferably SnO2 and / or ZnO.
[0058] In the method for producing surface-modified metal oxide nanoparticles, step 2 is a process for modifying the surface of the metal oxide nanoparticles obtained in step 1, and may include steps of: step 2-1 of mixing the metal oxide nanoparticles with ultrapure water to prepare a solution; step 2-2 of adding the compound represented by Chemical Formula 1 to the solution to prepare a reaction solution; step 2-3 of refluxing the reaction solution; step 2-4 of separating a reaction product from the refluxed solution and washing the separated reaction product; and step 2-5 of drying the washed reaction product to obtain surface-modified metal oxide nanoparticles.
[0059] The reaction solution may contain 100 to 700 parts by weight of ultrapure water and 300 to 1,500 parts by weight of the compound represented by Chemical Formula 1 relative to 100 parts by weight of the metal oxide nanoparticles, and preferably contains 350 to 600 parts by weight of ultrapure water and 300 to 1,500 parts by weight of the compound represented by Chemical Formula 1 relative to 100 parts by weight of the metal oxide nanoparticles. The composition may contain 400 to 1,200 parts by weight of the compound, or more preferably, 350 to 550 parts by weight of ultrapure water and 450 to 850 parts by weight of the compound. Here, if the amount of ultrapure water used is less than 100 parts by weight, the solvent may not be sufficiently refluxed during the surface modification process, and the surface modification may not be performed uniformly. If the amount of ultrapure water used is more than 700 parts by weight, the reflux reaction time may be too long. If the amount of the compound used is less than 300 parts by weight, the degree of modification of the surface of the metal oxide may be very insufficient or non-uniform, and the metal oxide particles may not be uniformly dispersed in the solvent and may precipitate. If the amount of the compound used is more than 1,500 parts by weight, it is uneconomical and may cause the solar cell element characteristics to deteriorate due to unreacted compounds, so it is better to use it within the above range.
[0060] The 2-3 stage reflux reaction can be carried out at 80 to 140° C., preferably 80 to 120° C. Here, if the reflux reaction temperature is less than 80° C., there may be a problem that the reflux is not sufficiently performed, and if it exceeds 140° C., there may be a problem that the surface of the metal oxide is excessively modified, hindering the operation of the solar cell element. The appropriate reflux reaction time is about 1 to 4 hours, preferably about 1.5 to 3 hours.
[0061] The separation and / or washing steps 2 to 4 may be performed by a common method used in the art. In one embodiment, the separation and / or washing may be performed by collecting the reflux reaction product from the reaction solution by centrifugation, and then washing the product with ultrapure water, etc.
[0062] The drying steps 2 to 5 can be carried out by a common method used in the art. In one embodiment, the reaction product obtained after washing can be heated in an oven at 50 to 80°C.
[0063] The coating agent for forming the electron transport layer as described above may be coated by a common solution coating method such as spin coating, blade coating, bar coating, spray coating, gravure coating, die coating, etc. In one embodiment, after coating, a heat treatment process may be performed at 200° C. or less to form an ultra-thin film having a thickness of 100 nm or less, preferably 1 to 40 nm, and more preferably 1 to 20 nm.
[0064] In the method for producing a perovskite solar cell of the present invention, the one-step stack can also be formed by forming a drain electrode on a conductive substrate, and then sequentially forming the hole transport layer, the perovskite light absorbing layer, and the electron transport layer as described above on the drain electrode.
[0065] Here, the conductive substrate may be a commonly used conductive substrate in the art. For example, a transparent plastic substrate made of a material such as polyethylene terephthalate, polyethylene naphthalate, polyethersulfone, aromatic polyester, or polyimide, a glass substrate, a quartz substrate, or a silicon substrate may be used.
[0066] The drain electrode may be made of at least one material selected from the group consisting of conductive metals, conductive metal alloys, metal oxides, and conductive polymers. Preferred examples of the material include ITO (Indium Tin Oxide), FTO (Fluorine doped Tin Oxide), ATO (Sb2O3 doped tin oxide), GTO (Gallium doped tin oxide), ZTO (tin doped zinc oxide), ZTO:Ga (gallium doped ZTO), IGZO (Indium gallium zinc oxide), IZO (Indium doped zinc oxide) and / or AZO (Aluminum doped zinc oxide).
[0067] The electron transport layer formed in one step is preferably formed to a thickness of 100 nm or less, preferably 1 to 40 nm, and more preferably 1 to 20 nm. Here, if the thickness of the electron transport layer exceeds 100 nm, there may be a problem that the short-circuit current Jsc and open circuit voltage Voc of the solar cell are reduced, so it is better to form the electron transport layer within the above-mentioned thickness range.
[0068] The surface of the coating layer thus formed, i.e., the electron transport layer, can be formed with very low roughness, and can satisfy the RMS (root mean square) roughness of 25 nm or less, preferably 17.0 to 25.0 nm, and more preferably 17.5 to 24.0 nm.
[0069] Next, in the method for manufacturing a perovskite solar cell of the present invention, the above-mentioned second step is a step of forming a transparent thin conductive barrier layer on the upper part of the electron transport layer through a deposition process, and the conductive barrier layer is made of ITO (Indium Tin Oxide), FTO (Fluorine), or the like. doped Tin Oxide), ATO(Sb2O3doped Tin Oxide), GTO(Gallium doped Tin Oxide), ZTO(tin doped zinc oxide), ZTO:Ga(gallium doped ZTO), IGZO(Indium gallium zinc oxide), IZO(Indium doped zinc oxide) or AZO(Aluminum The transparent insulating film may be a transparent thin film on which doped zinc oxide is vapor-deposited.
[0070] Here, the deposition may be performed by a common deposition process used in the art, and preferably, the deposition may be performed by using a sputtering method under the conditions of a process temperature of 100° C. or less, an RF power of 100 to 300 W, a process pressure of 1 to 3 mTorr, and an argon (Ar) flow of 10 to 40 sccm.
[0071] Furthermore, the surface of the conductive barrier layer can satisfy an RMS roughness of 30 nm or less, preferably 17.5 to 27.0 nm, and more preferably 18.0 to 25.0 nm.
[0072] The conductive barrier layer may have a low sheet resistance of 80 Ω / sq or less, preferably 76 Ω / sq or less, and more preferably 30.0 to 70 Ω / sq.
[0073] The conductive barrier layer formed in the two steps may have an average thickness of 50 to 110 nm, preferably 55 to 105 nm, more preferably 60 to 100 nm. Here, if the average thickness of the conductive barrier layer is less than 50 nm, the thickness is too thin, so that the effect of preventing the penetration of the electrode and ion migration due to the introduction of the conductive barrier layer is insufficient, or the sheet resistance increases, causing a problem of reduced device performance. In addition, if the average thickness of the conductive barrier layer exceeds 110 nm, the sheet resistance decreases and charge transfer becomes smooth, which is advantageous for device operation, but as the process time increases, damage to the light absorption layer may occur, resulting in a problem of reduced productivity. In the case of a tandem device, since the light receiving direction reaches the perovskite photoactive layer through the conductive barrier layer, unnecessary photocurrent loss may occur due to a thick conductive barrier layer, so it is better to form the conductive barrier layer by performing a deposition process to have an average thickness in the above range.
[0074] Next, in the manufacturing method of the perovskite solar cell of the present invention, the third step is a step of forming a source electrode on the upper part of the conductive barrier layer formed in the second step, and the source electrode can be formed by coating or evaporating one or more substances selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C, and conductive polymers.
[0075] In addition, in the configuration of the solar cell of the present invention, the source electrode is made of Pt, Au, Ni, Cu, A The insulating layer can be formed by coating or vapor deposition of one or more materials selected from the group consisting of Ga, In, Ru, Pd, Rh, Ir, Os, C and conductive polymers.
[0076] In addition, the solar cell of the present invention may further include a passivation layer between the light absorbing layer and the electron transport layer.
[0077] The present invention will be described in more detail below with reference to examples. However, it should be understood that the following examples are not intended to limit the scope of the present invention, but are merely intended to aid in the understanding of the present invention.
[0078] [Example] Example 1: Preparation of coating solution for forming electron transport layer (ETL) (1) Preparation of SnO2 nanoparticles SnCl4·5H2O was added to a beaker containing ultrapure water and stirred to prepare a metal precursor solution with a SnCl4 concentration of 0.33 M. Then, 35 ml of a basic aqueous solution of NH4OH was added to 265 ml of the metal precursor solution to prepare a reaction solution with a pH of approximately 8.0 to 8.5. The reactive solution was placed in a pressure vessel (autoclave or hydrothermal reactor) and hydrothermal synthesis was carried out at 180° C. for 12 hours. Next, the product obtained through the hydrothermal synthesis was washed 3 to 5 times with ultrapure water and ethanol to produce SnO2 nanoparticles. The average particle size of the produced SnO2 nanoparticles was 3-5 nm. In addition, a TEM measurement image of the produced SnO2 nanoparticles is shown in Figure 1, and the XRD measurement results are shown in Figure 2.
[0079] (2) Preparation of surface-modified SnO2 nanoparticles 8 g of the SnO2 nanoparticles prepared above were added to a round-bottom flask containing 40 mL of ultrapure water, and after stirring, 54 g of TFA (trifluoroacetic acid) was added to prepare a reaction solution. A condenser was attached to the round-bottom flask containing the prepared reaction solution, and the reaction was carried out at 90°C for 2 hours under reflux. Next, the reaction solution was centrifuged to separate the nanoparticles, and then dried in an oven at 60° C. to prepare surface-modified SnO 2 nanoparticles. In addition, the FT-IR measurement results of the surface-modified SnO2 nanoparticles produced are shown in Figure 3.
[0080] (3) Preparation of a dispersion solution (coating liquid) of surface-modified SnO2 nanoparticles 30 mg of the surface-modified SnO2 nanoparticles prepared above was added to 4 ml of isopropyl alcohol (dielectric constant ≦20) with low polarity, and then a dispersion-type coating solution for forming an electron transport layer (approximately 0.74 wt % of the surface-modified metal oxide) was prepared using an ultrasonic grinder. Also, a photograph of the dispersion type coating solution for forming the electron transport layer is shown in Figure 4b, and Figure 4a is a photograph taken after adding 30 mg of non-surface-modified SnO2 nanoparticles to isopropyl alcohol and dispersing them using an ultrasonic grinder.
[0081] Comparative Example 1 The SnO2 nanoparticles produced in Example 1(1) were prepared without a surface modification process. Next, 30 mg of the unmodified SnO2 nanoparticles was added to 4 ml of isopropyl alcohol, and then an ultrasonic grinder was used to prepare a dispersion-type coating solution for forming an electron transport layer. A photograph of the prepared coating solution is shown in Figure 4a.
[0082] Examples 2 to 3 and Comparative Examples 2 to 3 The coating solution for forming the electron transport layer was prepared in the same manner as in Example 1, but surface-modified SnO2 nanoparticles having the composition shown in Table 1 below were prepared, and then the surface-modified SnO2 nanoparticles were mixed with an organic solvent and then used in an ultrasonic grinder to prepare a dispersion-type coating solution for forming the electron transport layer, respectively, and Examples 2 to 3 and Comparative Examples 2 to 3 were carried out.
[0083] Comparative Example 4 Comparative Example 4 was carried out by preparing a coating solution for forming an electron transport layer in the same manner as in Example 1, except that the surface-modified SnO2 nanoparticles of Example 1 were mixed with ethyl alcohol having a dielectric constant of 25, and then a dispersion-type coating solution for forming an electron transport layer was prepared using an ultrasonic grinder.
[0084] [Table 1]
[0085] Experimental Example 1: Manufacturing of ultra-thin films and measurement of surface roughness and light transmittance of coating layers Each of the coating solutions prepared in the examples and comparative examples was spin-coated on a glass substrate and a perovskite thin film including the glass substrate, and then heat-treated at 30° C. to prepare an ultra-thin film having a thickness of 20 nm.
[0086] Next, the surface roughness of the ultrathin film (electron transport layer) formed on the top of the perovskite thin film including the glass substrate was measured using a non-contact method, and then the root-mean-square (rms) value of the roughness was calculated. The surface roughness was measured at three arbitrary points, and the average surface roughness values of the three measured points are shown in Table 2 below.
[0087] In addition, the ultra-thin film formed on the glass substrate was scanned with near-infrared light by a UV spectrum measurement method to measure the absorbance and light transmittance (%) of the sample. The results are shown in Table 2 below. The measurement results of the light transmittance for Example 1 This is shown in Fig. 5. Here, the light transmittance is the light transmittance at a wavelength of 500 to 550 nm.
[0088] [Table 2]
[0089] Looking at the RMS roughness and light transmittance in Table 2, it was confirmed that in the cases of Examples 1 to 3, the RMS roughness was 18.0 to 23.0 nm, which was a very low surface roughness, and the light transmittance was 90% or more, which was excellent optical properties.
[0090] In contrast, in the case of Comparative Example 2, which is a coating solution using surface-modified SnO2 nanoparticles prepared by using only 270 parts by weight (less than 300 parts by weight) of TFA during the synthesis of the surface-modified SnO2 nanoparticles, there was a problem that not only was the light transmittance low, but the roughness was relatively very high and the surface-modified SnO2 nanoparticles were not uniformly dispersed compared to Example 1 or Example 2. In addition, in the case of Comparative Example 3, which used 1570 parts by weight (more than 1500 parts by weight) of TFA, the roughness increased and there were some parts where the light transmittance was reduced, compared to Example 3, which is believed to be due to the aggregation phenomenon between some nanoparticles in the surface-modified SnO2 nanoparticles.
[0091] In addition, in the case of Comparative Example 4, the SnO2 particles were not dispersed, and the aggregated particles were coated on the upper end of the glass substrate in an island form, so that a thin film was not formed.
[0092] Manufacturing Example 1: Manufacturing of inverted perovskite solar cells An organic substrate (thickness 1.1 mm, 15.0 Ω / sq) coated with indium tin oxide (ITO) to a thickness of about 110 nm as a source electrode was cleaned in acetone and isopropyl alcohol (IPA) sequentially using an ultrasonic cleaner for 1 hour each.
[0093] Next, a hole transport layer (NiO) with a thickness of 30 nm was formed on the drain electrode by E-beam vacuum deposition. x ) was formed.
[0094] Next, a yellow light absorbing layer solution was formed by dissolving dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) on the top of the hole transport layer by spin coating, and then heat-treated at 100°C for 20 minutes to form a NiOx hole transport layer and a light absorbing layer (CsMAFAPbI) having a perovskite crystal structure with a thickness of 450 to 500 nm. x Br 3-x (0 ≦x≦3) was formed.
[0095] Next, the surface-modified coating solution prepared in Example 1 was spin-coated on the upper part of the perovskite light absorbing layer at 1,500 rpm for 1 minute, and then heat-treated at 30° C. to form an electron transport layer having an average thickness of 20 nm.
[0096] Next, a sputtering process (process conditions: process temperature 95-98°C, RF power 200-250W, process pressure 2.2-2.4mTorr, argon flow rate 25-30sccm) of IZO (Indium doped zinc oxide) was performed on the top of the electron transport layer to form a transparent evaporated thin film (conductive barrier layer) with an average thickness of 88nm.
[0097] Next, 1×10 silver (Ag) was added to the top of the conductive barrier layer. -7 The source electrode was formed by depositing the layer to a thickness of 100 nm under a pressure of 100 torr, thereby fabricating an inverted perovskite solar cell in which a drain electrode, hole transport layer, light absorption layer, electron transport layer, conductive barrier layer, and source electrode were stacked in this order.
[0098] The electron transport layer surface of the produced solar cell had an RMS of about 19.2 nm, and the conductive barrier layer surface had an RMS of about 23.4 nm.
[0099] In addition, SEM measurement images of the surface of the electron transport layer of the fabricated solar cell and the cross-sectional structure of the solar cell are shown in Figure 6, A and B.
[0100] Comparative Manufacturing Example 1 The drain electrode, the hole transport layer and the perovskite light absorbing layer were formed in the same manner as in Preparation Example 1.
[0101] Next, a passivation layer (C) with a thickness of 13 nm is formed on the top of the light absorbing layer by thermal evaporation. 60 ) was formed.
[0102] Next, the surface-modified coating solution prepared in Example 1 was spin-coated on the conductive barrier layer at 1,500 rpm for 1 minute, and then heat-treated at 30° C. to form an electron transport layer having a thickness of 20 nm.
[0103] Next, 1×10 silver (Ag) was added to the top of the conductive barrier layer. -7 The source electrode was formed by depositing the layer with a thickness of 100 nm at a pressure of 100 torr. The layer consisted of a drain electrode, a hole transport layer, a light absorption layer, and a passivation layer (C 60 They fabricated an inverted-structure perovskite solar cell in which a gate electrode, an electron transport layer, and a source electrode were stacked in that order.
[0104] The RMS of the electron transport layer surface of the produced solar cell was approximately 20.0 nm.
[0105] In addition, SEM measurement images of the surface of the electron transport layer of the fabricated solar cell and the cross-sectional structure of the solar cell are shown in Figure 7, A and B.
[0106] Production Examples 2 to 6 and Comparative Production Examples 2 to 4 An inverted-structure perovskite solar cell was manufactured in the same manner as in Manufacturing Example 1, but when forming the electron transport layer, the coating agents of Examples 2-3 and Comparative Example 1 were used instead of the coating agent of Example 1 to manufacture the solar cells in which the electron transport layer was formed, and Manufacturing Examples 2-6 and Comparative Manufacturing Examples 2-4 were carried out, respectively.
[0107] Experimental example 2: Measuring the performance of solar cells The current-voltage characteristics and efficiency of the solar cell manufactured in Manufacturing Example 1 were measured, and the results are shown in Table 3 below.
[0108] [Table 3]
[0109] Looking at the current-voltage characteristics and efficiency measurement results of the solar cells in Table 3, Production Examples 1 to 6 and Comparative Production Examples 1 and 2 exhibited a fill factor of 42.0FF or more and a photoelectric conversion efficiency of 7.0% or more, preferably a fill factor of 58 to 70FF and a high photoelectric conversion efficiency of 11.0% to 14.0%.
[0110] In addition, in the case of Comparative Manufacturing Example 3, in which the conductive barrier layer was formed at 48 nm, which is less than 50 nm, it was confirmed that there was a problem in that the fill factor and photoelectric conversion efficiency were significantly reduced compared to Manufacturing Example 1 (88 nm) and Manufacturing Example 4 (55 nm). This was because the sheet resistance increased significantly, hindering the movement of electrons collected in the electron transport layer, thereby significantly reducing the device efficiency.
[0111] In addition, in the case of Comparative Manufacturing Example 4 in which the conductive barrier layer was formed at 112 nm, which is greater than 110 nm, the sheet resistance was very low compared to Manufacturing Example 1 (88 nm) and Manufacturing Example 5 (105 nm), but the synergistic effect of the fill factor and photoelectric conversion efficiency was not observed and was reduced. However, this is believed to be because the process time or energy is increased to increase the thickness when forming the conductive barrier layer, which causes loss of the perovskite light absorbing layer and causes photocurrent loss due to the unnecessary thickness.
[0112] Experimental Example 3: Measurement of long-term storage stability of solar cells After the photoelectric conversion efficiency of each of the solar cells of Production Example 1 and Comparative Production Example 1 was measured in Experimental Example 2, the solar cells were left in a laboratory atmosphere at 25 to 28°C and atmospheric pressure, and the photoelectric conversion efficiency was then measured once a day. The measurement results of the photoelectric conversion efficiency after 14 days are shown in Table 4 below.
[0113] [Table 4]
[0114] As shown in Table 4, the photoelectric conversion efficiency measurement results show that in the case of Comparative Preparation Example 1 in which a passivation layer was formed between the photoactive layer and the electron transport layer, the photoelectric conversion efficiency (%) decreased by about 27.4%, and the long-term storage stability decreased. In contrast, in the solar cell of Preparation Example 1 in which a passivation layer was not formed between the photoactive layer and the electron transport layer and a conductive barrier layer was formed between the electron transport layer and the source electrode, the decrease rate of the photoelectric conversion efficiency was as low as 5.6%, which was very low. This confirmed that the present invention has superior long-term storage stability compared to conventional solar cells.
[0115] Manufacturing Example 7: Manufacturing of Tandem-structure Perovskite Solar Cells To fabricate a tandem solar cell, a silicon solar cell doped with n-type or p-type impurities is treated with hydrofluoric acid to form a SiO x After removing the oxide film, residual hydrofluoric acid was removed using ultrapure water, and a thin recombination layer was formed on the top of the silicon solar cell from which the oxide film had been removed using a sputtering process.
[0116] Next, a hole transport layer (NiOx ) was formed.
[0117] Next, a yellow light absorbing layer solution was formed on the top of the hole transport layer by spin coating using dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). The solution was then heat-treated at 100° C. for 20 minutes to form a NiO x A hole transport layer and a light absorbing layer (CsMAFAPbI) with a perovskite crystal structure with a thickness of 450 to 500 nm were x Br 3-x (0 ≦x≦3) was formed.
[0118] Next, the surface-modified coating solution prepared in Example 1 was spin-coated on the upper part of the perovskite light absorbing layer at 1,500 rpm for 1 minute, and then heat-treated at 30° C. to form an electron transport layer having an average thickness of 20 nm.
[0119] Next, IZO (Indium doped zinc oxide) was sputtered on the top of the electron transport layer (process conditions: process temperature 95-98°C, RF power 200 A transparent evaporated thin film (conductive barrier layer) having an average thickness of 88 nm was formed by performing a process using a 1000 W power supply, a process pressure of 2.2 to 2.4 mTorr, and an argon flow rate of 25 to 30 sccm.
[0120] Next, 1×10 silver (Ag) was added to the top of the conductive barrier layer. -7 The deposition was performed at a pressure of 100 torr to a thickness of 100 nm, and a source electrode was formed, thereby manufacturing a tandem-structured perovskite solar cell in which a silicon solar cell, recombination layer, hole transport layer, light absorption layer, electron transport layer, conductive barrier layer, and source electrode were stacked in this order.
[0121] Although specific embodiments have been illustrated and described above, the present invention is not limited to the above-described embodiments, and those skilled in the art may make various modifications and variations without departing from the spirit and scope of the technical ideas of the present invention as set forth in the following claims.
Claims
1. The present invention includes a stacked body in which a hole transport layer, a perovskite light absorbing layer, an electron transport layer, and a source electrode are stacked in this order, A conductive barrier layer is formed between the source electrode and the electron transport layer, The electron transport layer is a SnO layer whose surface is modified with a compound represented by the following Formula 1: 2 Contains nanoparticles, the surface-modified SnO 2 nanoparticles have an average particle size of 2-10 nm; The surface of the electron transport layer has a root mean square (RMS) roughness of 25 nm or less; A perovskite solar cell, characterized in that when the thickness of the electron transport layer is 20 to 30 nm, the light transmittance for a wavelength of 500 to 550 nm is 90 to 95%. 【Chemistry 1】 In the above formula 1, R 1 to R 5 are each independently a halogen atom; and n is an integer of 0 to 5.
2. The conductive barrier layer is made of indium tin oxide (ITO), fluorine doped tin oxide (FTO), or antimony oxide (ATO). 2 O 3 The perovskite solar cell according to claim 1, wherein the perovskite solar cell is a transparent thin film formed by vapor deposition of any one of the following: Ga-doped tin oxide, GTO (gallium doped tin oxide), ZTO (tin doped zinc oxide), ZTO:Ga (gallium doped ZTO), IGZO (indium gallium zinc oxide), IZO (indium doped zinc oxide) or AZO (aluminum doped zinc oxide).
3. The perovskite solar cell according to claim 1, characterized in that the electron transport layer has an average thickness of 100 nm or less, and the conductive barrier layer has an average thickness of 50 to 120 nm.
4. The perovskite solar cell as described in claim 1, characterized in that the surface of the conductive barrier layer has an RMS (root mean square) roughness of 30 nm or less.
5. The perovskite solar cell according to any one of claims 1 to 4, characterized in that the perovskite solar cell is a pin-structured perovskite solar cell, an inverted structured perovskite solar cell, a tandem perovskite solar cell or a tandem silicon / perovskite heterojunction solar cell.
6. The perovskite solar cell is an inverted structure perovskite solar cell, The perovskite solar cell according to claim 5, comprising a structure in which a drain electrode, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, a conductive barrier layer and a source electrode are stacked in order.
7. the perovskite solar cell is a tandem silicon / perovskite heterojunction solar cell; The perovskite solar cell according to claim 5, comprising a structure in which a drain electrode, a silicon solar cell, a recombination layer, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, a conductive barrier layer and a source electrode are stacked in order.
8. forming an electron transport layer by coating an electron transport layer-forming coating agent on the perovskite light absorbing layer of the laminate including the hole transport layer and the perovskite light absorbing layer; forming a transparent thin conductive barrier layer on the electron transport layer by a deposition process; forming a source electrode on top of the conductive barrier layer; The coating agent for forming the electron transport layer contains 0.50 to 3.00 wt % of a surface-modified metal oxide having an average particle size of 2 to 10 nm and the remaining amount of an organic solvent, The surface-modified metal oxide is prepared by carrying out a process including: a step of preparing metal oxide nanoparticles; and a step of reacting the metal oxide with a compound represented by the following formula 1 to prepare surface-modified metal oxide nanoparticles: The second step includes steps of: mixing the metal oxide nanoparticles with ultrapure water to prepare a solution (step 2-1); adding a compound represented by Formula 1 to the solution to prepare a reaction solution (step 2-2); refluxing the reaction solution (step 2-3); separating a reaction product from the refluxed solution and washing the separated reaction product (step 2-4); and drying the washed reaction product to obtain surface-modified metal oxide nanoparticles (step 2-5). The method for producing a perovskite solar cell is characterized in that the reaction solution in the 2-2 step contains 100 to 700 parts by weight of ultrapure water and 300 to 1,500 parts by weight of the compound represented by Chemical Formula 1, relative to 100 parts by weight of metal oxide nanoparticles. 【Chemistry 2】 In the above formula 1, R 1 to R 5 are each independently a halogen atom; and n is an integer of 0 to 5.
9. The method for producing a perovskite solar cell according to claim 8, wherein the coating is performed by a solution coating process.
Citation Information
Patent Citations
Perovskite solar battery and manufacturing method therefor
JP2018190928A
Method of manufacturing perovskite silicon tandem solar cell
KR1020180130397A
Tin oxide nano-thin film, Method for manufacturing the same and photoelectric device including the same
KR102127490B1